Trauma and mental disorder: multi-perspective depictions in Top Boy - Quadros, Wesley; Ogunwale, Adegboyega; Sule, Akeem (Frontiers in Psychiatry, 2024)
Psychiatry has often had an uneasy relationship with popular culture as depictions of mental health may be stigmatising and inaccurate. A recent critically acclaimed series, Top Boy, set in a crime-filled fictional housing estate in the London Borough of Hackney offers an informed and fairly balanced insight into broad mental health-related themes including racial trauma embodied in social inequities, the syndemic of mental disorder, substance misuse and gang-based crime as well as the psychosocial ramifications of illustrated mental health conditions. From both idiographic and nomothetic perspectives, Top Boy touches on a rich variety of structural determinants of mental health, as well as individual and environmental predisposition to mental disorder and substance misuse. The show offers an opportunity for education for both the broader society and the groups which suffer these syndemics. An understanding of how structural factors epidemiologically affect what psychiatric conditions individuals are likely to suffer, how they can be better reached by psychiatric services, and what interventions can help improve the socioeconomic factors that lead to the behaviours/paths that individuals end up is vital for public mental health policy.